Drought mitigation in Morocco: setting an indicator for an early drought warning - Chafai Elalaouim A.; Ibrahimy A.; Berkane A. (Drought management: scientific and technological innovations, 2008)
In order to alleviate the adverse effects of drought on agriculture in Morocco, we have developed an Indicator for an Early Drought Warning, based on the prediction of the three main cereal yields at any time of the growing season for a given Province. By comparison of the predicted yield with the statistical yield series, we can determine the drought severity and issue an Early Drought Warning when the predicted yield falls in the moderate or severe drought classes.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)